Review of antiviral peptides for use against zoonotic and selected non-zoonotic viruses - Hollmann, Axel; Cardoso, Nancy; Espeche, Juan C.; Maffía, Paulo C. (Elsevier, 2022)
Viruses remain one of the leading causes of animal and human disease. Some animal viral infections spread sporadically to human populations, posing a serious health risk. Particularly the emerging viral zoonotic diseases such as the novel, zoonotic coronavirus represent an actual challenge for the scientific and medical community. Besides human health risks, some animal viral infections, although still not zoonotic, represent important economic loses to the livestock industry. Viral infections pose a genuine concern for which there has been an increasing interest for new antiviral molecules. Among these novel compounds, antiviral peptides have been proposed as promising therapeutic options, not only for the growing body of evidence showing hopeful results but also due to the many adverse effects of chemical-based drugs. Here we review the current progress, key targets and considerations for the development of antiviral peptides (AVPs). The review summarizes the state of the art of the AVPs tested in zoonotic (coronaviruses, Rift Valley fever viruses, Eastern Equine Encephalitis Virus, Dengue and Junín virus) and also non-zoonotic farm animal viruses (avian and cattle viruses). Their molecular target, amino acid sequence and mechanism of action are summarized and reviewed.